The Application of Ultrasonic Waves and Microwaves to Improve Antihyperglycaemic and Antimicrobial Activities of Marrubium vulgare Extracts - Aleksandra Gavarić; Jelena Vladić; Jelena Vujetić; Dragan Radnović; Ana Volarić; Jelena Živković; Katarina Šavikin; Senka Vidović (Antibiotics, 2022)
Having scarce information about ultrasound assisted extraction (UAE) and microwave assisted extraction (MAE) of white horehound (Marrubium vulgare L.), the idea has emerged to determine the optimal process parameters for the maximization of polyphenols and to compare the efficiency of these green extraction technologies. The optimal UAE parameters are temperature of 73.6 °C, extraction time of 40 min and ultrasound power of 30.3 W/L, while the optimal MAE parameters are 63.8% ethanol, extraction time of 15 min and microwave power of 422 W. Extract obtained at optimal UAE parameters shows the highest antihyperglycemic activity (α-amylase inhibition: 50.63% and α-glucosidase inhibition: 48.67%), which can potentially be explained by the presence of chlorogenic acid and quercetin, which were not identified in the macerates. The most sensitive bacterial strain to optimal ultrasonic extract is Bacillus cereus, whereas the most sensitive fungal strain is Saccharomyces cerevisiae.